Ekonomiczne aspekty zrównoważonego rozwoju gospodarstwa (przedsiębiorstwa) rolniczego - Kondraszuk, Tomasz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
In the paper, the economic aspects of the sustainable development of farms were presented. The overuse of natural resources does not raise costs in the short run. The problem is to reconcile the goals of individual farmers to social and environmental goals. The formation of compatible criteria should be based on synergy and joint benefits. A sound approach to the economic account and the understanding of the real farm's goals permits to respect the claims of all interested parties. Satisfactory economic solutions must ensure development of farms and increase of farms incomes in the long run. Agricultural policy and finance allocated into agriculture will have a large impact on the real sustainable development of agriculture.